The Ups and Downs of the Nigerian Society: A Satirical View on Socio-political Matters in Chimamanda Ngozi Adichie’s Purple Hibiscus (2004) and Sefi Atta’s a Bit of Difference (2013) - Babacar Diakhate (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This paper aims to show the objectivity of Nigerian writers by portraying the ups and downs of their society. Indeed, in Sefi Atta’s a Bit of Difference and Chimamanda Ngozi Adichie’s Purple Hibiscus, the authors have done a diagnosis without complaisance of the bottlenecks that impede Nigeria from moving forwards.   It also demonstrates that feminist activism can challenge a political military power. It finally displays that violence at universities; social injustice, corruption and mediocrity are the evils that characterized the Nigerian society.